A comparative study on usage of cowdung ash and wood ash as partial replacement in flyash brick. (2021) - Indhiradevi, P.; Manikandan, P.; Rajkumar, K.; Logeswaran, S.
Abstract: This research project presents the results on a comparative study for the use of Cow dung Ash and Wood ash as partial replacement in the production of Fly ash brick. Cow dung are often wont to manufacture bricks which are eco-friendly and far cheaper. Cow dung ash is obtained by drying cow dung under sun then burning it. Huge amount of ash generation are causing waste disposal problems. Cow dung is employed as fuel for the domestic purpose, which generates solid waste as ash. Wood ash is that the inorganic and organic residue remaining after combustion of wood or unbleached wood fiber. The physical and chemical properties of wood ash vary significantly counting on many factors. Through this study an effort was made to match the properties of the ash brick adding the wood ash and cow dung ash as a partial replacement. The method of manufacturing traditional bricks from kiln is expensive and causes pollution. Using cow dung ash and Wood ash the pollution caused by the development materials are often decreased to a far extent. We used 5%, 10%, 15% and 20% of Cow dung ash and Wood ash and therefore obtained maximum strength at 5% replacement of Cow Dung ash and 15% replacement of wood ash. Studies were done to acknowledge the properties of bricks using fly ash with partial replacement of cow dung ash and Wood ash. In this project we are trying to compare and study the effective properties of brick by introducing Cow dung ash and Wood ash as supplementary materials in the fly ash brick.